THE ROLE OF THE CENTRAL JAVA PROVINCIAL WAGE COUNCIL IN DETERMINING REGENCY/CITY MINIMUM WAGES IN 2020 - AGUS PRAMONO (UNTAG Law Review, 2020)
The purpose of the study entitled "The Role of the Central Java Provincial Wage Council in Determining Regency/City Minimum Wages in 2020" is to determine the role of the Central Java Provincial Wage Council and the procedures for setting the minimum wage in 2020 by the Governor of Central Java Province. The research method used is normative juridical, which is an approach aimed at the study of legal issues from the aspect of applicable legal regulations, in this case in the form of the role of the Central Java Provincial Wage Council in seeking regency/city minimum wages in Central Java. Before the Central Java Provincial Wages Council was formed the name of the Central Java Provincial Research, Wages and Welfare Commission. With Presidential Decree No. 107 of 2004 concerning the Wages Board stipulated by the President of the Republic of Indonesia Megawati Sukarno Putri on 18 October 2004. In principle between the Research Commission and the Wage Council there are some differences, among others, regarding the requirements to become a member of the Research Commission and the Wage Board that the requirements to become members of research do not have to bachelor, while to become a member of the Wage Board must be a S1 as well as regarding the composition in the Research Commission the ratio between representatives of workers, government and employers is 1:1:1 and universities. While in the Wage Council the ratio of government, workers, and employers is 2: 1: 1 and universities and experts. In order to follow up on the Presidential Decree on the Wage Council, the Governor of Central Java Province issued Decree No. 560/61/2005 concerning the Establishment of the Central Java Provincial Wage Council. The Governor of Central Java Province also issued Regulation No. 31 of 2005 concerning Procedures for Proposing Members of the Central Java Province Wage Council. Governor's Decree Number 560/58 2019, concerning UMK of 35 Regencies/Cities in 2020 stipulated the highest wage in Semarang City of Rp. 2,715,000,-, while the lowest was found in the Banjarnegara district of Rp. 1,748,000. Determination of wages has been through existing mechanisms and refers to applicable laws and regulations. The minimum wage is calculated based on the formula of Article 44 paragraph (2) of Government Regulation no. 78 of 2015, in accordance with the Minister of Manpower Letter No. BM 305 Year 2019.